Effect of Normal and Shear Interaction Stiffnesses on Three-Dimensional Viscoplastic Creep Behaviour of a CFR Dam - Memduh Karalar; Murat Çavuşli (Advances in Civil Engineering)
Rockfill materials and foundation continuously interact with each other during lifetime of the rockfill dams. This interaction condition alters the viscoplastic behaviour of these dams in time. For this reason, examination of the time-dependent viscoplastic interaction analyses is vital important for monitoring and evaluating of the future and safety of the rockfill dams. In this study, it is observed how the time-dependent displacement and stress behaviour of a concrete-faced rockfill (CFR) dam change by the effect of the normal and shear interaction spring stiffness parameters. Ilısu Dam that is the longest concrete-faced rockfill dam in the world now and has been completed in the year 2017 is selected for the three-dimensional (3D) creep analyses. The 3D finite difference model of this dam is modelled using FLAC3D software that is based on the finite difference method. The concrete slab, rockfill materials, foundation, and reservoir water are separately created for the 3D interaction analyses. A WIPP-creep viscoplastic material model and a burger-creep viscoplastic material model that are special material models for the creep analyses of rockfill dams are used for concrete slab and for rockfill materials and foundation, respectively. Totally 20 different interaction parameters (normal and shear stiffnesses) are separately defined between the rockfill materials and the foundation to represent the interaction condition. According to numerical analyses, the effect of these various interaction parameters on the viscoplastic behaviour of the Ilısu Dam is evaluated for the empty and full reservoir conditions. As a consequence, the most critical normal and shear stiffnesses’ range for creep analyses of the rockfill dams is determined. Afterwards, the long-term viscoplastic interaction behaviour of Ilısu Dam is examined during 35 years considering this important stiffness values. Settlements, horizontal displacements, and principal stresses are evaluated for both reservoir conditions, and these results are compared with each other in detail.